The Writing Mentoring Program: - Eva Kuntschner; Brigitte Römmer-Nossek (Educare)
In 2013, the University of Vienna’s Centre for Teaching and Learning (CTL) implemented a pilot project, which has since grown to become the core of the university’s academic writing services for students. The writing mentoring programme was designed with the goal to create a means for disseminating knowledge about writing processes amongst students in earlier stages of their studies. The programme’s organisational structure is based on the experience that, to ensure scalability, an institution as large as the University of Vienna (approx. 90.000 students) needs to rely on multipliers and on the cooperation of stakeholders in its many academic departments. Regarding the writing mentoring programme, this translates into a focus on the processes of academic writing and sensitivity towards disciplinary cultures. In this position paper, we aim to demonstrate how writing mentoring can be implemented to provide structures which allow advanced Bachelor and Master-students to support other students’ academic writing in meaningful ways. In this way, a programme like ours can help in transforming organisational practices.